A practical guide for medical teachers - Dent, John A., MMedEd; Harden, Ronald M. (Edinburgh : Elsevier Churchill Livingstone, 2005)
Changes occur in both healthcare delivery and in the context and methods in which medicine is taught and learned. This book attempts to bridge the gap between the theoretical aspects of medical education, and its attendant jargon, and the practical delivery of enthusiastic teaching. It is for clinicians and other healthcare teachers in general
SECTION 1 CURRICULUM DEVELOPMENT 1. New horizons in medical education R. M. Harden, J. A. Dent 2. Curriculum planning and development R. M. Harden 3. The undergraduate curriculum S. Leinster 4. The postgraduate curriculum Author to be confirmed 5. Continuing professional development D. Davis SECTION 2 LEARNING SITUATIONS 6. Lectures J. A. Dent 7. Small group teaching J. R. Rudland 8. Clinical skills teaching J. A. D. Dent, G. Adamo 9. Bedside teaching J. A. D. Dent !0. Ambulatory care teaching J. A. D. Dent 11. In the community P. Worley 12. Distance education J. Laidlaw, E. A. Hesketh 13. Peer-assisted learning A. Cumming, Michael Ross SECTION 3 EDUCATIONAL STRATEGIES 14. Outcome-based education S. Smith 15. Independent learning R. M. H. Harden 16. Problem-based learning A. Sefton 17. Integrated learning D. Prideaux 18. Multiprofessional/interprofessional education H. Barr 19. Core curriculum and student-selected components R. Jordan, Suzanne Cholerton SECTION 4 TOOLS AND AIDS 20. Instructional design A. Stewart 21. Study guides J. Laidlaw, E. A. Hesketh 22. Computer-assisted learning D. Dewhurst 23. Simulators Author to be confirmed 24. e-learning D. Davies SECTION 5 CURRICULUM THEMES 25. Basic sciences P. McCrorie 26. Communication skills J. Ker, D. Snadden 27. Ethics and attitudes M. Brennan 28. Preparing for practice M. McMurdo, M. Witham 29. Informatics F. Sullivan, E. Mitchell 30. Evidence-based medicine P. Glasziou, C. Heneghan SECTION 6 ASSESSMENT 31. Principles of assessment M. Friedman Ben-David 32. Standard setting J. Norcini 33. Choosing assessment instruments S. McAleer 34. Written assessments L. Schuwirth, C. van der Vleuten 35. Performance assessment Meredith Marks, Susan Humphrey-Murto 36. Work-based assessment M. Davis 37. Portfolios, projects and dissertations M. Davis 38. External examiners C. D. Forbes SECTION 7 STAFF AND STUDENTS 39. Student selection I. C. McManus 40. Student support S. Rennie, J. A. D. Dent 41. Study skills R. Bandaranayake 42. Staff development Y. Steinert 43. Academic standards S. Mennin 44. Research and publication J. Bligh, J. Brice Appendix of useful websites Index
Includes bibliographical references and index.
Keywords: Medicine -- Study and teaching